2015
DOI: 10.15761/god.1000138
|View full text |Cite
|
Sign up to set email alerts
|

Blue light therapy versus low dose isotretinon in mild to moderate acne

Abstract: Background: Despite advances in acne therapy, treatment failure is still common. Isotretinoin is the only drug that affects almost all factors in acne pathogenesis, however side-effects are common at the doses reported in published studies in the literature. Sun exposure is known to be beneficial for acne. Lasers/light-based devices may offer an alternative to conventional acne modalities in selected patients, such as non-responder or noncompliant patients or in antibiotic resistant patients. The aim of the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Photothermal therapies: fractional erbium glass laser 1550 nm, Nd:YAG laser 1064 nm and 1320 nm and diode laser 1450 nm . Photochemical therapies: blue light 405–420 nm . Photochemical/photothermal therapies (multifactorial effects): potassium titanyl phosphate laser (KTP) 532 nm, intense pulsed light (IPL) 530–1200 nm, Pulsed Dye Laser (PDL) 585–595 nm .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Photothermal therapies: fractional erbium glass laser 1550 nm, Nd:YAG laser 1064 nm and 1320 nm and diode laser 1450 nm . Photochemical therapies: blue light 405–420 nm . Photochemical/photothermal therapies (multifactorial effects): potassium titanyl phosphate laser (KTP) 532 nm, intense pulsed light (IPL) 530–1200 nm, Pulsed Dye Laser (PDL) 585–595 nm .…”
Section: Resultsmentioning
confidence: 99%
“…Although these results initially seem contradictory, this can be explained by the different nature of the treatments in terms of devices and settings (0.350 ms shows more pronounced effect on capillaries than 10 ms). Furthermore, four studies compared laser‐ and light‐based therapy to pharmacological therapy (isotretinoin, clindamycin, benzoyl peroxide and a combination of benzoyl peroxide and tretinoin). None of these studies found convincing differences between study groups, indicating that no treatment group was more superior to the other.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Acne is a multifaceted disorder of the sebaceous glands, which is common in young people . A variety of topical and systemic modalities have been used in treating acne.…”
mentioning
confidence: 99%